Musculoskeletal Manifestations in COVID-19 Patients at Paramilitary Hospital: A Cross-sectional Study - KC, Samir; Shrestha, Sailendra Kumar Duwal; Nepal, Prabin; Karki, Umash; Karki, Netra Bahadur; Mahaseth, Adarsha (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: Musculoskeletal symptoms are frequently reported in patients with COVID-19; however, evidence from low-resource settings remains limited. This study aimed to assess the spectrum and severity of musculoskeletal manifestations in RT-PCR–confirmed COVID-19 patients in Nepal and examine their association with disease severity.Methods: A hospital-based cross-sectional study was conducted at Nepal Armed Police Force Hospital, Kathmandu, from April 15 to July 15, 2022. After ethical approval from Nepal Health Research Council (Reference number: NHRC-3644). All adult patients (≥18 years) with confirmed COVID-19 were enrolled. Individuals with pre-existing chronic pain disorders, pregnancy, or altered sensorium were excluded. New-onset musculoskeletal symptoms myalgia, arthralgia, low back pain, fatigue, and paresthesia were recorded and graded using the Visual Analogue Scale for pain and the Numerical Rating Scale for fatigue. Demographic and clinical data, including comorbidities and COVID-19 severity, were collected. Associations were analyzed using ANOVA and chi-square tests (p < 0.05).Results: Among 250 patients, there were 119(47.60%) male; mean age 49.80±18.1 years, most had mild 150(60%) or moderate 71(28.40%) COVID-19, while 29(11.60%) had severe illness. Myalgia 175(70%), arthralgia 158(63.20%), and fatigue 153(61.20%) were the most prevalent musculoskeletal symptoms. Low back pain was reported in 110(44%) and paresthesia in 11 (4.40%). Mean symptom severity scores increased significantly with disease severity (p < 0.001 for all). All of the moderate and severe cases had myalgia, arthralgia, and fatigue.Conclusions: Musculoskeletal manifestations are common in COVID-19 and increase significantly with disease severity. These findings highlight the need for symptom monitoring in moderate and severe cases.